Acute hemorrhagic leukoencephalitis with gradual symptom onset: Case Report and literature review - Sannes, Ida; Harr, Marianne E.; Antal, Ellen-Ann; Beyer, Mona K.; Nordengen, Kaja (Frontiers in Neuroscience, 2025)
This report highlights an atypical case of acute hemorrhagic Leukoencephalitis (AHLE) in a 73-year-old male, contributing valuable insights into the disease’s progression in older adults. AHLE, a rare and often fatal central nervous system disorder typically affecting younger individuals, with a median age of 33. Our patient experienced atypical subacute symptoms over 3 months, the longest duration reported, and ultimately achieved a functional outcome with a modified Rankin Scale (mRS) score of 2. A comprehensive review of 152 cases available through PubMed, revealing a 58% mortality rate with a median survival of just 2 days, and a mean mRS of 4.3, though survivor exhibited a more favorable mean mRS of 1.8. Only 6% of cases had a subacute onset of 3 weeks or more.